TMOs@Gr/Cu composites: Microstructure and properties. (15th November 2019) - Zhang, Yu; Li, Yan; Li, Yanchun; Song, Meihui; Zhang, Xiaochen; Zhang, Weijun
Abstract: In this work, a new material -TMOs@Gr/Cu composites (TMOs represents transition metal oxides, M = Co, Sn, Mn; @ means hybriding; Gr means graphene) were prepared by the method of powder metallurgy after TMOs hybriding graphene through hydrothermal synthesis, and then the microstructure and properties of TMOs@Gr/Cu composites were studied compared with Gr/Cu composites. The results revealed that the TMOs nano-particles which adsorbed on the surface of graphene exhibited a good adhesion effect in the composite materials. An obvious tendency could be found that TMOs inhibited effectively the aggregation of grapheme. At the same time, the TMOs particles would not fall off during the preparation of composite materials. Therefore, compared with Gr/Cu composites, the properties of TMOs@Gr/Cu composites, such as density, hardness, thermal conductivity had been enhanced. The properties of (Co3 O4  + SnO2 )@Gr/Cu composites were listed as followed: density 89.7%, hardness 185HBW, thermal conductivity 139 W/(m°C). The properties of (Co3 O4  + MnO2 )@Gr/Cu composites were: density 91.7%, hardness 242HBW, thermal conductivity 151 W/(m·°C). However, the electrical conductivity of TMOs@Gr/Cu composites decreased due to a large number of crystal defects. Graphical abstract: Unlabelled Image Highlights: Graphene hybrided by transition metal oxides reinforcing copper matrix (TMOs@Gr/Cu) composites are designed and prepared. Graphene hybrided by two kinds of transition metal oxides (TMOs@Gr) compounds is used as reinforcement in the composites. Hybrid graphene possesses high-density and good dispersion. TMOs@Gr/Cu composites achieve excellent relative density (91.7%), hardness (242 HBW) and thermal conductivity (151 W/(m·°C)). TMOs@Gr/Cu composites' electrical conductivity is low because of a large number of crystal defects in the matrix.